Foreign Is Not Unfamiliar. A Translation Impact Study Involving Taiwan Subjects - Wang, Qianting; Chen, Hui-Wen; Zhong, Yong (Meta, 2009)
AbstractThe research discussed in this paper is the last of a trilogy investigating the impact of foreignized and domesticated translations on sampled readers. The two precursors had been conducted in two Chinese Mainland cities (Beijing and Guangzhou) and this last one was conducted in the Taiwanese city of Douliou. Therefore, comparisons can be made with the two precursors in the discussion of the research procedure and findings of the Taiwan project. The paper begins with a brief introduction of the background in which the Taiwan project was conceived and a brief profile of the subjects sampled for the project. Then there is a description of the research design, including the hypotheses and field work methodology. Four hypotheses were tested: a) the subjects would have distinguishable ideas about the two renditions; b) they would have a more intense feeling of exoticism when reading the foreignized rendition; c) their degree of sensing the rendition to be exotic or not would be correlated with their other socio-linguistic perceptions of that text; d) the findings of the present investigation would corroborate those obtained from the two precursors. The description of the research design is followed by a presentation of the data analysis conducted for the project together with a statement of the conventions adopted for reading the statistics. Based on the data analysis, interpretations are made in relation to the hypotheses.